Exploring Consumers’ Interest in Choosing Sustainable Food - Hsu, Shih-Yun; Wang, Huai-Chen; Ho, Juei-Ling; Chen, Ho-Cheng (Frontiers in Psychology, 2020)
In order for humans to achieve a healthier diet and maintain ecological balance, a new concept regarding sustainable food is introduced. The aim of this study is, therefore, to explore consumers’ interests for choosing sustainable food. Due to time and resource constraints, the study utilizes “DoSurvey”, an internet survey platform, to distribute questionnaires. Survey invitations are sent out in a snowball manner. Invitations are posted in multiple online communities and forwarded by various members to other sites; 333 valid responses are collected. The results show that family and friend support and health incentive are the two strongest predictors for sustainable food buying interest. Price accessibility, on the other hand, has no impact on interest. This is not to say that price accessibility does not influence behavior. It just means that it is not the factor that fosters interest. Once an individual is interested, she/he may still rely heavily on price accessibility in purchasing sustainable food.